Proximity: Revealing new mobile meanings of a traditional news concept. Issue 5 (3rd July 2016) - Oppegaard, Brett; Rabby, Michael K.
Abstract : Proximity has helped practitioners and scholars to determine newsworthiness for generations. Emerging mobile technologies, though, with contextual-awareness capabilities, have been complicating many of the related issues and expanding the realm of journalistic content—as well as conceptualizations of timeliness—through growing digital tethers to place and use of that material in place. Those evolving complexities include the increasing possibilities for journalists to make connections to contemporary audiences through the customization of content based on matters of user location. In turn, where an audience member is located when media is delivered can matter greatly. Geolocation metadata has become ubiquitous and media delivery systems can sort that data to customize user experiences based on place. In terms of such tailoring, mobile devices allow novel kinds of personalized connections to journalism, prompted by a geographical nearness to physical stimuli. In response, this study examines the potential of proximity for impact on key factors of engagement, through the involvement, social facilitation, and satisfaction of users. This conceptualization of mobile journalism shows that media designers now not only can know precisely where their particular audience is but also adapt their messages to the situation as a way to generate more engaging experiences.